Mouse hepatic cells support assembly of infectious Hepatitis C virus particles - Long, Gang; Hiet, Marie-Sophie; Windisch, Marc P.; Lee, Ji Young; Lohmann, Volker; Bartenschlager, Ralf (Gastroenterology, 2011)
Background & Aims - Hepatitis C virus (HCV) has a high propensity to establish persistence; better understanding of this process requires the development of a fully permissive and immunocompetent small animal model. Mouse cells can be engineered to express the human orthologs of the entry molecules CD81 and occludin to allow entry of HCV. However, RNA replication is poor in mouse cells, and it is not clear whether they support assembly and release of infectious HCV particles. We used a trans-complementation-based system to demonstrate HCV assembly competence of mouse liver cell lines. - Methods - A panel of 3 mouse hepatoma cell lines that contain a stable subgenomic HCV replicon was used for ectopic expression of the HCV structural proteins, p7, nonstructural protein 2, and/or apolipoprotein E (apoE). Assembly and release of infectious HCV particles was determined by measuring viral RNA, proteins, and infectivity of virus released into the culture supernatant. - Results - Mouse replicon cells released low amounts of HCV particles, but ectopic expression of apoE increased release of infectious HCV to levels observed in the human hepatoma cell line Huh7.5. Thus, apoE is the limiting factor for assembly of HCV in mouse hepatoma cells but probably not in primary mouse hepatocytes. Products of all 3 human alleles of apoE and mouse apoE support HCV assembly with comparable efficiency. Mouse and human cell-derived HCV particles have similar biophysical properties, dependency on entry factors, and levels of association with apoE. - Conclusions - Mouse hepatic cells permit HCV assembly and might be developed to create an immunocompetent and fully permissive mouse model of HCV infection.
Gesehen am 10.10.2022